Evolution of the potassium channel gene Kcnj13 underlies colour pattern diversification in Danio fish - Marco Podobnik (Nature Portfolio, 2020)
Fish show an amazing variety of colour patterns; however, the genetic basis for the evolution of this diversity is largely unexplored. Here, the authors identify the potassium channel gene Kcnj13 as evolved to contribute to differences in colour patterns between closely related Danio fish species.